Comprehensive Crystal Regulation Reduces Interfacial Energy Loss for Efficient Blue Perovskite Light‐Emitting Diodes - Tang, Ying‐Yi; Shen, Yang; Yu, Yi; Zhang, Kai; Wang, Bing‐Feng; Tang, Jian‐Xin; Li, Yan‐Qing (Small (Weinheim an der Bergstrasse, Germany), 2024)
As an essential component of future full‐color displays, blue perovskite light‐emitting diodes (PeLEDs) still lag far behind the red and green counterparts in the device performances. In the mainstream quasi‐2D blue perovskite system, trap‐mediated nonradiative loss, low energy transfer efficiency, and interface fluorescence quenching remain significant challenges. Herein, guanidinium thiocyanate (GASCN) and potassium cinnamate (PCA) are respectively introduced into the hole transport layer (HTL) and the perovskite precursor to achieve a dense and uniform perovskite thin film with greatly improved optoelectronic properties. Therefore, adequate GA+ acts as pre‐nucleation sites on the HTL surface, regulating crystallization through strong hydrogen bonding with perovskite intermediates. The realized polydisperse domain distribution is conducive to cascade energy transfer, and the improved hole transport ability alleviates interface fluorescence quenching. In addition, the SCN− and CA− groups can form coordination bonds with the defects at the buried perovskite interface and grain boundaries, respectively, which effectively suppresses the detrimental nonradiative recombination. Benefitting from the comprehensive crystal regulation, blue PeLEDs featuring stable emission at 484 and 468 nm exhibit improved external quantum efficiencies of 11.5% and 4.3%, respectively. Comprehensive crystal regulation is realized by simultaneously modifying the buried grain‐growth interface and grain boundaries, leading to uniform blue perovskite films with smooth exciton transfer and reduced trap states. Blue perovskite light‐emitting diodes are achieved with external quantum efficiencies of 11.5% at 484 nm and 4.3% at 468 nm, respectively.